(3eNJUQ ZjK GdCOH GdPi GfSLe aj TQM dGejI GdYLes - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s; (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s ((3GHi HcQ eMeO GdNWjH GdSefhOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOQ ef JCOH hHYO aEf GdbUjOI GdehSheI HdGejI GdYLe hbO TQMgG GdUaOi aGSJNQJ Gddg JYGdi hdg GdNjQI ai JdNjUg hJgPjHg s
(3BNQgG (B:s
(3GdeYfi bO QHhc dGeQ Gf cfJ JYde HGWf GdGeQ ai eQGOge efc aGgQH efge hdG JWGhYge s
(3GdfSNI HgG MhGTs
(3HChdgG agQSs
(3HgG fXGe GdJYbjHIs
(3dGejI GdYLe deDjO GdOjf CHj GSeGYjd GdMSjf Hf Ydi GdWZQGFi SfI (B514 s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdCOHs